Case report: improvement of cardiac remodeling with shock wave therapy of a patient with ischemic cardiomyopathy - Bai, Yingnan; Wang, Xiaoyan; Deng, Xin; Wu, Hongyi; Fathy, Abdel Hamid; Xi, Yan; Zou, Yunzeng; Cui, Jie; Ge, Junbo (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Percutaneous coronary intervention (PCI) and coronary-artery bypass grafting (CABG) are two major preferred reperfusion strategies to restore the ischemic-related artery patency, but PCI and CABG do not necessarily guarantee the recovery of post-procedure left ventricular (LV) dysfunction and release of symptoms. Moreover, there is no definitive effective way to enhance microcirculations. Theoretically, shock wave therapy (SWT) is an option. We report here a case of patient who received SWT. The patient’s medical history was characterized by chest pain for 20 years, having received CABG 13 years ago. The follow-up angiography showed all blood vessels are stiff and rigid therefore no chance for a second CABG. After cardiac SWT treatment for 1 year, the patient’s symptoms of chest pain and chronic heart failure significantly improved, the odds of cardiac muscle survival increased, the cardiac remodeling was also improved. What’s more, left ventricular ejection fraction (LVEF) was improved from 34% to 51% and 43% in half year and 1 year after SWT which is indicated by single-photon emission computed tomography (SPECT), respectively. To our knowledge, this is the first report of 2-cycle cardiac SWT treatments over 1 year with a complete follow-up, indicating that SWT can not only improve the symptoms of chronic heart failure, but also improve LVEF and cardiac remodeling caused by ischemic cardiomyopathy.